Kinetic Study of Blue Methylene Adsorption Using Coconut Husk Base Activated - Anselmus Boy Baunsele; Erly Grizca Boelan; Aloisius Masan Kopon; Rahayu Rahayu (Indonesian Journal of Chemical Research, 2022)
Blue methylene is a cationic dye. It usually used for various industries. The waste of blue methylene can reduce the environmental balance expecialy for aquatic biota by inhibition the penetration of sunlight to the water. Most natural ingridients and method was used to reduce the existence of the dye. In this research, coconut husk was activated with NaOH solution then used for blue methylene adsorption. The coconut husk activated aims to reduce the polluter on the adsorbent to increase the capacity of adsorption. The study result showed that the optimum adsorption of blue methylene at pH 7 for 75 minutes of adsorption with the capacity adsorption of 1,41 mg g-1. The result of kinetic study described that the adsorption process according to second order pseudo reaction kinetic model with the adsorption constant rate of 2,54 x 10-4 g mg-1 minute-1